Public health emergency preparedness a practical approach for the real world - McKinney, Suzet; Papke, Mary Elise (Burlington, MA Jones & Bartlett Learning, 2019)
"This is a widely offered upper level undergrad and grad level course. Will bundle perfectly with our PH Disaster Casebook by Linda Landesman. Will be a gritty practical text"--Provided by publisher
What is public health preparedness? -- Legal issues in public health emergency preparedness -- Chemical, biological, radiological, nuclear and explosive (CBRNE) events -- Natural disasters and unintentional emergencies -- Pandemic influenza -- Epidemiology and surveillance in preparedness and response -- Hazard assessment and planning -- Training, exercising and evaluating -- Multi-agency coordination systems, information sharing, and interoperability -- Community preparedness and recovery -- Crisis and emergency risk communication -- Medical countermeasures -- Medical surge -- Leadership and the future of public health preparedness
Includes bibliographical references and index
Keywords: Emergency management; Civil Defense; Emergencies; Emergency Medical Services